Evaluation of complacency about dental implants with shared decision making and satisfaction scores: A cross-sectional study - Mohammed A AlSarhan; Razan S. Alaqeely; Reham AlJasser; Dalal H Otaibi; Saleh AlOraini; Ibraheem F. Alshiddi (Elsevier, 2021)
Background: The dentist-patient relationship is delicate. Engaging the patient in the dental treatment planning especially for lengthy procedures as dental implants improves the relation as well as treatment outcomes including patient satisfaction. We aimed at evaluating the importance of Shared Decision making (SDM) and level of satisfaction among dental implant patients by employing SDM and satisfaction scores. Materials & Methods: The present cross-sectional study was pursued between April 2019 to September 2019, among dental implant patients (n = 144) who have completed their prosthetic part of implant treatment with at least 3 months of post-restoration evaluation. Demographic and implant data were collected from electronic filing system (Salud) as well as measurement of SDM score. Data were analyzed using SPSS 24.0 version statistical software. Results: The mean satisfaction score was higher for implant placement with Periodontists (31.9%). However, among surgical specialist the mean satisfaction score was found to be higher for oral surgeons who had 1-5 years of experience (46.5%). Patients reported that their decision making was greatly influenced by the treating dentist. A statistical significance was found where (64.6%) of Implant patients would like to undergo the procedure again (p < 0.0001). Conclusion: Shared decision-making and patient satisfaction enables the treatment delivery to be more effective and ethical, in addition to being patient-centered care.